2018
DOI: 10.1016/j.epsl.2018.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Glacial chronology and production rate cross-calibration of five cosmogenic nuclide and mineral systems from the southern Central Andean Plateau

Abstract: Glacial deposits on the high-altitude, arid southern Central Andean Plateau (CAP), the Puna in northwestern Argentina, document past changes in climate, but the associated geomorphic features have rarely been directly dated. This study provides direct age control of glacial moraine deposits from the central Puna (24°S) at elevations of 3900-5000 m through surface 1 11 production rates for 21 Ne in pyroxene and quartz for the high, (sub-)tropical Andes. The production rates are based on our 10 Be-normalized pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 54 publications
(98 reference statements)
4
33
0
Order By: Relevance
“…The calculated exposure times of the Jordanian chert nodules are equivalent to erosion rates of ∼ 4-12 mm kyr −1 (Table 2), consistent with other rates measured in the region (Matmon and Zilberman, 2017, and references therein). Calculation of paleo-erosion rates is not as straightforward, as Miocene cherts were sampled post-deposition and represent exposure both during erosion from bedrock and transport in the Hazeva River.…”
Section: Modern and Miocene Erosion Rates And The Influence Of Climatsupporting
confidence: 87%
“…The calculated exposure times of the Jordanian chert nodules are equivalent to erosion rates of ∼ 4-12 mm kyr −1 (Table 2), consistent with other rates measured in the region (Matmon and Zilberman, 2017, and references therein). Calculation of paleo-erosion rates is not as straightforward, as Miocene cherts were sampled post-deposition and represent exposure both during erosion from bedrock and transport in the Hazeva River.…”
Section: Modern and Miocene Erosion Rates And The Influence Of Climatsupporting
confidence: 87%
“…However, humid periods during the Pleistocene and Holocene enabled glaciation in the Altiplano (e.g., Ammann et al, 2001; Kull & Grosjean, 2000; Rodbell et al, 2009). Cosmogenic nuclide exposure dating of moraines in the Peruvian‐Bolivian Altiplano indicate that the greatest glacial extent during the Local Glacial Maximum (LGM) was prior to 26 ka (Luna et al, 2018; Smith et al, 2005; Zech et al, 2009). However, moraine chronologies in the Argentinean‐Bolivian Altiplano (e.g., Blard et al, 2009, 2014; Zech et al, 2009) indicate late readvances, synchronous with a regional humid period (Tauca Period 17–15 ka, Sylvestre et al, 1999; Placzek et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that during glacial periods, the Intertropical Convergence Zone (ITCZ) over South America had shifted far southward (Broccoli, Dahl, & Stouffer, ) leading to enhanced moisture transport via the South‐American low‐level jet and increased moisture availability in the highlands of NW Argentina (Haselton, Hilley, & Strecker, ; Vizy & Cook, ). However, the interior of the orogen was not affected by this increase in the same way as the orogenic flanks, as is shown by areally much more limited, and a westward‐decreasing impact of Pleistocene glaciations in the Puna Plateau (Haselton et al., ; Luna et al., ). This is compatible with the notion of existing effective orographic barriers along the eastern Andean plateau area: The existence of these barriers and resulting diversions of atmospheric flow patterns results in decreased moisture availability towards the orogen interior.…”
Section: Discussionmentioning
confidence: 80%